2023
DOI: 10.1021/acs.est.2c07152
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Folate Modifies the Association between Serum Per- and Polyfluoroalkyl Substances and Antibody Concentrations in U.S. Adolescents

Abstract: Per-and polyfluoroalkyl substances (PFAS) exposure has been associated with reduced antibody levels. Higher red blood cell (RBC) folate was previously associated with lower serum PFAS concentrations in adolescents. This study included 819 adolescents aged 12−19 years who had detectable rubella and measles antibody levels in serum from the U.S. National Health and Nutrition Examination Survey 2003−2004 and 2009−2010 cycles.We found inverse associations between serum PFOS and PFHxS and rubella antibodies, betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…A recent study reported that higher PFAS concentrations were associated with lower antibody levels to rubella and mumps among adolescents with lower red blood cell folate levels but not in adolescents with higher folate levels in the US general population. 17 In addition to neural tube defect prevention, these cumulative findings suggest that adequate folate status may counteract PFAS adverse effects and possibly the adverse effects associated with other environmental pollutants, as reported in experimental research. [56][57][58] The mechanisms by which folate interacts with PFAS in birth outcomes are unclear and need further experimental investigation.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…A recent study reported that higher PFAS concentrations were associated with lower antibody levels to rubella and mumps among adolescents with lower red blood cell folate levels but not in adolescents with higher folate levels in the US general population. 17 In addition to neural tube defect prevention, these cumulative findings suggest that adequate folate status may counteract PFAS adverse effects and possibly the adverse effects associated with other environmental pollutants, as reported in experimental research. [56][57][58] The mechanisms by which folate interacts with PFAS in birth outcomes are unclear and need further experimental investigation.…”
Section: Discussionmentioning
confidence: 85%
“…These results support our hypothesis that higher prenatal folate status could reduce or counteract PFAS exposure in birth outcomes. A recent study reported that higher PFAS concentrations were associated with lower antibody levels to rubella and mumps among adolescents with lower red blood cell folate levels but not in adolescents with higher folate levels in the US general population . In addition to neural tube defect prevention, these cumulative findings suggest that adequate folate status may counteract PFAS adverse effects and possibly the adverse effects associated with other environmental pollutants, as reported in experimental research …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations